PREDICTING HEALTH RELATED QUALITY OF LIFE IN INDONESIAN POST MYOCARDIAL INFARCTION PATIENTS - Devi Wulandari; Adriana Soekandar Ginanjar; Urip Purwono; Baydhowi Baydhowi; Fredrick Dermawan Purba (Journal of Educational, Health and Community Psychology, 2019)
Myocardial infarction is one of chronic illnesses that has a major impact to patient’s health related quality of life. This study tested three psychosocial factors (i.e. religious coping behaviour, cardiac anxiety and marital satisfaction) and two disease-related factors (i.e. left ventricular ejection fraction, comorbidity) in predicting health related quality of life in patients with post myocardial infarction in Indonesia. A cross sectional study included 170 patients with myocardial infarction was conducted. The patients completed four questionnaires: MacNew Health Related Quality of Life, Couple Satisfaction Index, Cardiac anxiety Questionnaire, and religious coping behaviour. The theoretical model was tested using structural equation modelling.  Results revealed that cardiac anxiety was negatively associated with health-related quality of life. Marital satisfaction was a significant moderator in the relationship between cardiac anxiety and health related quality of life. There were no significant relationships among patient’s comorbidity, left ventricular ejection fraction, religious coping behaviour and health related quality of life. Results of the study shed the light of the importance of protective effects of patient’s immediate environment in shaping patient’s health related quality of life.